1)Al2O3 + 6HCl = 2AlCl3 + 3H2O
Al2O3 + 6H(+) + 6Cl(-) = 2Al(+3) + 6Cl(-) + 3H2O
Al2O3 + 6H(+) = 2Al(+3) + 3H2O
2) Ba(NO3)2 + K2CO3 = BaCO3 + 2KNO3
Ba(+2) + 2NO3(-) + 2K(+) + CO3(-2) = BaCO3 + 2K(+) + 2NO3(-)
Ba(+2) + CO3(-2) = BaCO3
3) 3K2CO3 + 2H3PO4 =2 K3PO4 +3 CO2 + 3H2O
6K(+) + 3CO3(-2) + 6H(+) + 2PO4(-3) = 6K(+) + 2PO4(-3) + 3CO2 + 3H2O
3CO3(-2) + 6H(+) = 3CO2 + 3H2O
4) H3PO4 +3 KOH = K3PO4 +3 H2O
3H(+) + PO4(-3) + 3K(+) + 3OH(-) = 3K(+) + PO4(-3) + 3H2O
3H(+) + 3OH(-) = 3H2O
5) K2CO3 + BaCl2 = BaCO3 + 2KCl
2K(+) + CO3(-2) + Ba(+2) + 2Cl(-) = BaCO3 + 2K(+) + 2Cl(-)
Ba(+2) + CO3(-2) = BaCO3
1)Al2O3 + 6HCl = 2AlCl3 + 3H2O
Al2O3 + 6H(+) + 6Cl(-) = 2Al(+3) + 6Cl(-) + 3H2O
Al2O3 + 6H(+) = 2Al(+3) + 3H2O
2) Ba(NO3)2 + K2CO3 = BaCO3 + 2KNO3
Ba(+2) + 2NO3(-) + 2K(+) + CO3(-2) = BaCO3 + 2K(+) + 2NO3(-)
Ba(+2) + CO3(-2) = BaCO3
3) 3K2CO3 + 2H3PO4 =2 K3PO4 +3 CO2 + 3H2O
6K(+) + 3CO3(-2) + 6H(+) + 2PO4(-3) = 6K(+) + 2PO4(-3) + 3CO2 + 3H2O
3CO3(-2) + 6H(+) = 3CO2 + 3H2O
4) H3PO4 +3 KOH = K3PO4 +3 H2O
3H(+) + PO4(-3) + 3K(+) + 3OH(-) = 3K(+) + PO4(-3) + 3H2O
3H(+) + 3OH(-) = 3H2O
5) K2CO3 + BaCl2 = BaCO3 + 2KCl
2K(+) + CO3(-2) + Ba(+2) + 2Cl(-) = BaCO3 + 2K(+) + 2Cl(-)
Ba(+2) + CO3(-2) = BaCO3
дано
V(C2H5OH) = 143.75 mL
p(C2H5OH) = 0.8 g/mL
m(C2H5Br)-?
C2H5Br+NaOH-->C2H5OH+NaBr
m(C2H5OH) = V(C2H5OH) * p(C2H5OH) = 143.75 * 0.8 = 115 g
M(C2H5OH) = 46 g/mol
n(C2H5OH) = m/M = 115 / 46 = 2.5 mol
n(C2H5Br) = n(C2H5OH) = 2.5 mol
M(C2H5Br)= 109 g/mol
m(C2H5Br) = n*M = 2.5 * 109 = 272.5 g
ответ 272.5 г